2003
DOI: 10.1046/j.1464-410x.2003.04131.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term results of orthotopic neobladder reconstruction after radical cystectomy

Abstract: RESULTSIn all, 102 patients underwent radical cystectomy with orthotopic neobladder reconstruction in the study period; their mean (range) follow-up was 73 (36-144) months. Neobladder substitution was with an ileocaecal segment in 35 patients, sigmoid colon in 34 and ileum in 33. Early complications occurred in 32 patients (31%) although open surgical intervention was required in only nine (9%). The death rate after surgery was 3.9%. Late complications occurred in 31 patients (30%) and were primarily caused by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
50
3
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(68 citation statements)
references
References 16 publications
13
50
3
2
Order By: Relevance
“…This could be partly explained by the short observation period in this study compared with those in other series. Furthermore, there were no significant differences in the incidences of either early or late complications among patients with different types of NB, which is also consistent with previous studies [1,2,8] . In addition, if complications would be divided into surgical related and not, there were no significant differences in the incidences of each type of complications among patients with different types of NB (data not shown).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This could be partly explained by the short observation period in this study compared with those in other series. Furthermore, there were no significant differences in the incidences of either early or late complications among patients with different types of NB, which is also consistent with previous studies [1,2,8] . In addition, if complications would be divided into surgical related and not, there were no significant differences in the incidences of each type of complications among patients with different types of NB (data not shown).…”
Section: Discussionsupporting
confidence: 92%
“…To date, a number of studies have reported the clinical outcomes in patients undergoing reconstruction of intestinal orthotopic NB following radical cystectomy [3][4][5][6][7] ; however, there have been few reports comparing longterm outcomes among patients receiving different types of NB creation [8,17,18] . Since 1983, orthotopic NB reconstruction has been performed in more than 400 patients who were treated with radical cystectomy for invasive bladder cancer at our institutions, suggesting that the outcomes obtained from our data may reliable and comparable with other studies performed in high-volume centers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Post-operative continence was deWned according to Kulkarni et al (2003). No patient reported preoperative incontinence.…”
Section: Follow-upmentioning
confidence: 99%
“…In dieses Kollektiv gingen alle Patienten ein, die in diesem Zeitraum an einem muskelinvasiven Urothelkarzinom litten, also einschließlich derjenigen mit lymphatisch metastasiertem oder fernmetastasiertem Befund. Liegt keine lymphatische oder Fernmetastasierung vor und ist das lokale Tumorstadium <pT4, werden auch Kollektive mit 5-Jahres-Überlebensraten >80% beschrieben [2,3] …”
Section: Alternativen Zur Zystektomieunclassified